Descrição de recursos bibliográficos em MARC 21: estratégias de conversão para formatos de intercâmbio multiplataforma - Ferreira, Jefferson Leite Oliveira (2018)
The objective of this research is to define strategies for converting bibliographic records from MARC 21 format to MARCXML, Metadata Authority Description Schema (MADS) and Metadata Object Description Schema (MODS) metadata schemas, through name and subject authority as analysis categories. The mapping of the subfields with their respective values and the subsequent collation with the tags of the metadata schemes target of the conversion were done. The exploratory and descriptive research provided by bibliographical and documentary surveys adopts systematic observation as a technique that enables the empirical stage. It ad-dresses the entity-relationship model adopted by the Functional Requirements for Biblio-graphic Records (FRBR) as a tool to model the relationship between the attributes of the metadata under study and the MARC format with the requirements of Functional Require-ments for AuthorityDescription (FRAD) and the Functional Requirements for Subject Authority Data (FRSAD) for the topics subject authority data. The preliminary analysis showed that the flexibility of the schemas allows to treat redundancies and ambivalences in the representation of personal names and their attributes. It also allows the approach through appropriate refer-ences and qualifiers with emphasis on aspects related to synonymy and polysemy of subject headings. It analyzes the notational flexibility of related schemas such as Metadata Encoding and Transmission Standard (METS) in the wake of the perspective of interoperable infor-mation resources. It inserts the Dublin Core vocabulary into the discussion and coding of de-scriptive metadata, which made it possible to map the limits and possibilities of this vocabu-lary in the bibliographic context. The results of the conversions carried out illustrated the stra-tegic role of the entity-relationship model as a conceptual paradigm adopted by the FRBR and, in a subsidiary way, by the FRAD and FRSAD, in the process of mapping and coding the personal name and subject matter authority data from MARC to MADS and MODS. It was observed that all the analyzed MARC fields and subfields, besides finding their equiva-lents in the corresponding XML schemas, are added with relational attributes that demon-strated effectiveness in the links that associate authors to roles assumed in the resources. It concludes that the applied conversion strategies extract the semantic value of the relational paradigm advocated by the FRBR as a key element for the reach of expressiveness, internal coherence and sophistication of the syntactic and semantic relations so dear to the effectiveness of the catalogs. It suggests, from the literature consulted and the results verified in the empiri-cal stage, researches that aim to contemplate strategies of metadata conversion with emphasis in groups 2 and 3 of FRBR.